THE HARMONY OF NATIONAL VALUES IN MODERN FASHION DESIGN (Modern American Journal of Engineering, Technology, and Innovation, 2025)
In today’s era of globalization, national clothing has become more than just a means of dressing—it has emerged as a key symbol of cultural identity. This article explores the harmony between contemporary fashion trends and traditional national values. It examines the historical roots of national attire, its adaptation to modern fashion, and the role of fabrics and patterns in preserving cultural heritage. Furthermore, it discusses challenges related to dressing culture among the youth and evaluates this issue through the lens of fashion shows, events, and scholarly studies.